2019
DOI: 10.1111/jfs.12679
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of different interactions between Staphylococcus aureus phages and pomegranate peel, grape seed, and black cumin extracts

Abstract: Today, antibiotic resistance is one of the most crucial problems so that researchers have begun to search for alternatives to antibiotics. Among these alternatives, phage therapy and phytotherapy became prominent. The present study aims to put forward a different approach by combining these two methods. For this purpose, Staphylococcus aureus phages were isolated from commercial mixtures. After that, extraction of phenolic compounds from pomegranate peels (Ps), grape seeds (GSs), and black cumin (NS) was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…In the experiments, we observed that molasses increased phage plaque size and burst size at inhibitory and subinhibitory concentrations. Similar to our results, it was reported that black cumin (Nigella sativa) extract increase the plaque size of S. aureus phage (Tayyarcan et al 2019). In literature, antimicrobial agents like antibiotics, essential oil and plant extracts have been used for enhancing the phage therapy applications.…”
Section: R a F Tsupporting
confidence: 92%
See 1 more Smart Citation
“…In the experiments, we observed that molasses increased phage plaque size and burst size at inhibitory and subinhibitory concentrations. Similar to our results, it was reported that black cumin (Nigella sativa) extract increase the plaque size of S. aureus phage (Tayyarcan et al 2019). In literature, antimicrobial agents like antibiotics, essential oil and plant extracts have been used for enhancing the phage therapy applications.…”
Section: R a F Tsupporting
confidence: 92%
“…In the phage synergism studies in the literature, synergism was mostly studied with antibiotics, but natural antimicrobial agents were not studied much. In a few studies; honey, chestnut honey, various plant extracts, bacteriocin and phenolic substances were studied to demonstrate phage synergism (Tayyarcan et al 2019;Oliveira et al 2017Oliveira et al , 2018Heo et al 2018). Although phage synergism studies have been conducted before with substances containing antimicrobials, there is no such research with molasses.…”
Section: R a F Tmentioning
confidence: 99%
“…Due to the importance of S. aureus to cause diseases, the study of alternative ways to inhibit the growth of this pathogen has become necessary (Silva et al, 2017;Tong et al, 2015). Plant-derived bioactive compounds are promising, due to antimicrobial activity which have been generally demonstrated (Bouarab-Chibane et al, 2019;Garzón et al, 2020;Tayyarcan et al, 2019;Zola et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity is associated with the secretion of multiple virulence factors and the increasing resistance of S. aureus to various drugs is limiting treatment of infections (Wu et al, 2018). Hence, the development of alternative antimicrobial strategies involving new compounds has attracted great attention (Silva et al, 2017;Tayyarcan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When added as pure molecules, several PCs could induce proteome and transcriptome changes in probiotic LAB as well as commensal gut bacteria with significant effects on protein folding, cell wall synthesis and the production of exopolysaccharide and surface proteins [ 15 , 16 , 17 , 18 ]. Other authors also reported that bacterial cell surface alteration by PCs can modulate phage-host interactions in Lactobacillus casei [ 19 ] and more recently in Staphylococcus aureus [ 20 ]. Taking advantage of the recent isolation of lytic phages OE33PA [ 21 ] and Vinitor [ 22 , 23 ] infecting O. oeni , we explored the hypothesis that phage-host interactions may vary in the presence or absence of PCs.…”
Section: Introductionmentioning
confidence: 99%